Parametric study of carbide precipitation in 16wt% chromium ferritic stainless steel (FSS) welds - Amuda, Muhammed Olawale Hakeem; Mridha, Shahjahan (Trans Tech Publications, Switzerland, 2012)
Other than grain coarsening, the loss of corrosion resistance in ferritic stainless steel (FSS) welds due to intergranular precipitation of chromium carbides restricts the use of the alloy for structural application. The use of cryogenic cooling offers dual opportunities for the control of weld geometry and grain structure in FSS. This results in improved mechanical properties but the effect on carbide precipitation was not investigated. In this paper, the effect of heat flux, welding speed and flow rate of cryogenic liquid on carbide precipitation in 16% chromium FSS welds are discussed. The use of cryogenic cooling reduces the size of the sensitized zone but this is not significantly affected by the flow rate of the cryogenic fluid. Compared to the conventional welding, the cryogenic cooling increases the cooling rate and reduces the martensite content in the high temperature heat affected zone (HTHAZ) by about 20%. This results in wider ditched-structure in welds made with flow rates lower than 0.052L/min. Cryogenic cooling produces more ditched weld microstructure revealed by electrolytic etching in oxalic acid; however, the structure is acceptable since no single grain boundary is completely surrounded by ditches.